การออกแบบและพัฒนาหุ่นยนต์เดินบนระนาบแบบขนาน - ณัฐดนัย ตัณฑวิรุฬห์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The design of a walking robot is studied in this research. The study includes mechanism design, kinematics design and motion controller. The walking robot consists of two parallel planar frames with will be formed a 3-DOF motion, the position in planes at centroid and a rotation angle of the plane relative to the other. The robot motion is generated by controlling the relative motion of the two planar frames. The advantage of parallel frames walking robot over the insect-like robot is the fewer degree of freedoms needed in the parallel frames walking robot. This means that fewer actuators required. The accuracy tests of the robot itself consist of the measurement of motion error in different type of walking and turning or body rotation. The maximum error of walking in a 2-meter straight line is less than 1.5% and the error of turning or body rotation is less than 2.5 degree per revolution. This error dominated from the environment because of the lack of environment sensors such as sensors to detect robot positions relative to the reference frame.